Data supporting the publication 'Clay swelling: role of cations in stabilizing/destabilizing mechanisms' - Chen, Wenlong; Grabowski, Robert C.; Goel, Saurav (Cranfield University, 2022)
In the compressed dataset, there are two subdirectories, one in the name of 'Example' and another 'PostprocessData'. The Example directory contains input files, output data and postprocessed data for case Na12 starting at a d-space of onelayer value, where files starts with in.* are input files for lammps software, files ending with .dat or .lmptrj are output files from lammps, and files ending with .mat are matlab processed data. The 'postporcessedata' contains matlab processed results for all simulations in this study, contains simulation for NaMMT, KMMT, CaMMT and NaBD starting at onelayer, twolayer and threelayer d-space values.
Keywords: Clay Swelling'; 'Molecular Dynamic Simulations Reveal'; 'Molecular dynamics simulation analysis'; 'hydration'; 'Physical Chemistry of Materials'; 'Molecular Physics'; 'Nanochemistry and Supramolecular Chemistry'; 'Colloid and Surface Chemistry'; 'Mineralogy'; 'Natural Hazards'; 'Sedimentology'; 'Soil Chemistry (excl. Carbon Sequestration Science)'; 'Soil Physics'